ANALISIS MATERIAL REQUIREMENT PLANNING PRODUK COCONUT SUGAR PADA KUL-KUL FARM - Martha, Kukuh Anggara; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2018)
Raw material inventory is one of the important assets for the company, errors in raw material planning will lead to problems in the production process, it is important to do a good raw material inventory planning. One of the concepts that can be applied is by using the Material Requirement Planning (MRP) system. This study aims to: (1) Know and determine the amount of net demand for each raw material Coconut Sugar 150 gr / jar. (2) To know and determine the optimal order size for each raw material of Coconut Sugar product 150 gr / jar. (3) Knowing and determining the right time to do the ordering plan for each raw material of Coconut Sugar 150 gr / jar. (4) Knowing and determining the method that produces the lowest cost for Coconut Sugar product 150 gr / jar. The data used are quantitative and qualitative data obtained from interviews to some parties related to coconut sugar production and observation on the object under study. Data analysis technique used is descriptive analysis technique which explain systematically with stages namely: making Master Production Schedule, determination of net requirement, lot size determination (Lot for lot method and Part Period Balancing), determination of optimal lot sizing method, and determination of order time raw material or MRP table manufacturing process. The results showed: (1) The net requirement for each raw material was obtained from the difference between the gross requirement with the revenue plan and the lead time of each raw material. (2) The determination of the optimal order size for each raw material is done by using lot for lot method and part period balancing. (3) The determination of the ordering time of the raw materials is the same as making the MRP table for each raw material and is based on the lot sizing method which has been selected previously. (4) Comparison of the final result shows that the method of part-time balancing with total inventory cost of Rp 53,979 is the method that produces the lowest cost, when compared with the lot for lot method that generates total inventory cost of Rp 192.000, but especially for the raw material of coconut palm using Lot for lot method to avoid stored raw materials.